Keterampilan Menulis Laporan Penelitian Tindakan Kelas Guru di Kecamatan Plered Purwakarta - Rayi Siti Fitriani; Yudi Bachtiar; Gia Nikawanti (Universitas Sebelas Maret, 2019)
The teacher is an element that plays an important role in improving the quality of education in Indonesia. It is inevitable that there are various problems in learning that need to be solved by a teacher, one of them with research. Classroom Action Research is an attempt to correct any shortcomings and deficiencies in learning. Followed by writing a Classroom Action Research Report, carried out as an attempt to think and prove to improve the professionalism of teachers and is no less important as an added value in increasing credit. The aim of this study is to describe: teacher skills in writing Classroom Action Research reports and obstacles for teachers in writing scientific articles. This research is a qualitative research with a descriptive design. Based on the results of the study, it was concluded that the skills to write research reports in the classroom were still low and very rarely performed. The obstacles that the teacher encountered were the lack of understanding of scientific articles, little systematic writing knowledge, limited liability, problems with the use of computers and time. But of all that, the cause of the obstacles that the teacher encounters is motivation.